Carcinogênese bucal DMBA induzida com aplicação de imumonomodulador P-MAPA: análise histomorfométrica - Morelli, Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The incidence of oral cancer is extremely variable and in many parts of a public health problem. Squamous cell carcinomas are the most frequent oral cancer, constituting about 90% of cases, followed by others such as verrucous carcinoma and undifferentiated, and small salivaryagland tumors, sarcomas and rarely, malignant melanoma. According to the National Cancer Institute (INCA), oral cancer is the eighth highest incidence in Brazil. Every year there are over ten thousand new cases. The leading causes of cancer are attributable to environmental Prfluences, particularly those related to lifestyle, and regular daily use of alcohol and tobacco, poor oral hygiene, immune deficiencies, exposure to sun without protection, and genetic predisposition are the main factors that lead oral neoplasms. The aim of this study was to evaluate the immunomodulating effects of the drug P-MAP in experimental carcinogenesis induced in golden hamster sirius 7-12 hydrocarbon-Dimethyl Benzatraceno (DMBA) by histomorphometric analysis of chemically induced lesions in the region of Prtraoral purse. A total of 48 golden hamsters sirius (Mesocriatus auratus) were 24 males and 24 females with 60 days and a mean body weight of 100 grams. The animals were divided into six groups: three treated groups and three control groups, with 8 animals in each group, corresponding to three experimental periods in the range of 7, 16 and 22 weeks. At the end of time set by each group, animals were euthanized employing overdose of anesthetic (ketamine hydrochloride 10%) and muscle relaxant, Prtraperitoneally. Histological analysis was founded on the recognition of forms of structural components of tissues. This descriptive analysis has been very important to define morphological patterns, although it is very subjective and a histomorphometric analysis of the most accurate...

A incidência do câncer de boca é extremamente variável, sendo em muitas partes do mundo um problema de saúde pública. Os carcinomas espinocelulares são as neoplasias orais mais freqüentes, constituindo cerca de 90% dos casos, seguidos por outros carcinomas como os verrucosos e indiferenciados, e tumores de pequenasaglândulas salivares, sarcomas e raramente, por melanoma maligno. Segundo o Instituto Nacional do Câncer (INCA), câncer de boca é o oitavo de maior incidência no Brasil. A cada ano surgem mais de dez mil novos casos. As principais causas das neoplasias são atribuíveis arPrfluências ambientais, particularmente aquelas relacionadas ao estilo de vida, uso cotidiano e regular do álcool e do tabaco, má higiene bucal, deficiências imunológicas, exposição ao sol sem proteção e predisposição genética são os principais fatores que levam as neoplasias bucais .O objetivo do presente estudo foi avaliar aração imunomoduladora do medicamento P-MAPA em modelo experimental de carcinogênse induzida em hamster sírius dourados com hidrocarboneto 7-12-Dimetil Benzatraceno (DMBA) através de análise histomorfométrica das lesões quimicamente induzidas na região de bolsa intrabucal. Foram utilizados 48 hamsters sírius dourados (Mesocriatus auratus) sendo 24 machos e 24 fêmeas com 60 dias e um peso corporal médio de 100 gramas. Os animais foram distribuídos em seis grupos, sendo três grupos tratados e três grupos controles, apresentando 8 animais em cada grupo, correspondendo a três períodos experimentais no intervalo de 7, 16 e 22 semanas. Ao final de cada tempo estabelecido por grupo, os animais foram eutanasiados empregando-se overdose de anestésico (cloridrato de quetamina a 10%) e relaxante muscular, viarPrtraperitoneal. A análise histológica sempre se baseou no reconhecimento das formas dos componentes...
Keywords: Neoplasias; Cricetinae; Neoplasias bucais